Mal Pelayanan Publik: Peningkatan Aksebilitas Dan Keterjangkauan Layanan (Studi Pada Mall Pelayanan Publik Ramayana Jalan Merdeka Kota Malang) - Bintang Aldi; Wika Ananda; Bagus Kusuma; Aris Putra; H. Hayat (Universitas Warmadewa, 2024)
With integrated service functions at both the central and regional levels, the Public Service Mall is the center of public service activities for government administration. This also functions as an expansion of integrated service capabilities at both the central and regional levels. Apart from that, MPP services are integrated with information technology to overcome global problems caused by the Industrial Revolution 4.0. A variety of public services are offered by ministries, organizations, state, district and city governments, as well as state-owned, regional and private enterprises, at the Public Service Mall. Increasing service speed, convenience, reach, comfort and security is one of the goals. This type of research is called qualitative research with descriptive techniques, using research information and the observed behavior of research objects to produce descriptive data in the form of spoken and written words. The existence of the Public Service Mall has increased the speed, convenience, reach, comfort and safety of public services thereby providing benefits to the community, according to the findings of a study on the accessibility and affordability of services in the Ramayana Public Service. Mall in Malang City. The majority of Malang City residents think that the existence of a public service mall can directly improve services and support Malang City government policies to increase the effectiveness of public services.